2021
DOI: 10.3390/cells10113186
|View full text |Cite
|
Sign up to set email alerts
|

NR3C1 Glucocorticoid Receptor Gene Polymorphisms Are Associated with Membranous and IgA Nephropathies

Abstract: Glomerular diseases (GNs) are responsible for approximately 20% of chronic kidney diseases. Glucocorticoid receptor gene (NR3C1) single nucleotide polymorphisms (SNPs) are implicated in differences in predisposition to autoimmunity and steroid sensitivity. The aim of this study was to evaluate the frequency of the NR3C1 SNPs—rs6198, rs41423247 and rs17209237—in 72 IgA nephropathy (IgAN) and 38 membranous nephropathy (MN) patients compared to 175 healthy controls and to correlate the effectiveness of treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Missense variants can also affect the structure of the protein by affecting the interaction, stability, and solubility of the protein. To evaluate the effect of a missense mutation on protein structure and function, the SNPs are mapped into the protein structure and validated through in silico [ 27 , 28 , 29 ]. The human gene of TNF-α , NR3C1 , and CYP3A5 contains a total of 1119 missense mutations in the NCBI dbSNP database.…”
Section: Resultsmentioning
confidence: 99%
“…Missense variants can also affect the structure of the protein by affecting the interaction, stability, and solubility of the protein. To evaluate the effect of a missense mutation on protein structure and function, the SNPs are mapped into the protein structure and validated through in silico [ 27 , 28 , 29 ]. The human gene of TNF-α , NR3C1 , and CYP3A5 contains a total of 1119 missense mutations in the NCBI dbSNP database.…”
Section: Resultsmentioning
confidence: 99%
“…Genomics can also be used for phenotype-genotype correlation in kidney biopsies of patients with glomerular diseases. In a small Polish study, it was suggested that NR3C1 single nucleotide polymorphisms are associated with the clinical manifestations of IgAN and score in Oxford classification (Pac et al 2021 ).…”
Section: Omicsmentioning
confidence: 99%
“…In a small Polish study, it was suggested that NR3C1 single nucleotide polymorphisms are associated with the clinical manifestations of IgAN and score in Oxford classification (Pac et al 2021).…”
Section: Genomicsmentioning
confidence: 99%
“…GCs can modulate inflammatory gene expression through several distinct mechanisms. Many single nucleotide polymorphisms (SNPs) of the NR3C1 gene have already been found to be directly or indirectly related (through GC action or GC resistance) to different mental disorders, especially the stress-related ones and autoimmune diseases such as multiple sclerosis, systemic lupus erythematosus, rheumatoid arthritis, inflammatory bowel disease, and membranous nephropathy [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Recent bioinformatics studies have suggested that there are several polymorphisms in the NR3C1 gene, as well as in other genes such as TNF, CYP3A5 and FKBP5 , that have deleterious potential to cause GC resistance [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%